2018
DOI: 10.1136/esmoopen-2018-000332
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose nivolumab can be effective in non-small cell lung cancer: alternative option for financial toxicity

Abstract: ObjectivesNivolumab is used at 3 mg/kg or fixed doses of 240 mg every 2 weeks. There was no dose–response/toxicity relationship of nivolumab. This study evaluated the efficacy of low-dose nivolumab as an alternative to the financial toxicity of standard-dose nivolumab in treatment of non-small cell lung cancer (NSCLC).MethodsOutcomes of patients with NSCLC treated with nivolumab as a routine practice at two tertiary hospitals in Korea were retrospectively analysed. Patients who could not afford standard nivolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 24 publications
(20 reference statements)
2
56
0
Order By: Relevance
“…In lung cancer, it is licensed for the treatment of locally advanced or metastatic non-small cell lung cancer (NSCLC) after prior chemotherapy. Two large randomised studies in patients with advanced non-squamous (NSq) NSCLC (CheckMate057 [3]) and squamous (Sq) NSCLC (CheckMate017 [4]) comparing nivolumab to docetaxel have demonstrated its efficacy at extending overall survival (OS) [5,6], and the interest of nivolumab in treating NSCLC has been confirmed in many subsequent studies in routine clinical practice [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In lung cancer, it is licensed for the treatment of locally advanced or metastatic non-small cell lung cancer (NSCLC) after prior chemotherapy. Two large randomised studies in patients with advanced non-squamous (NSq) NSCLC (CheckMate057 [3]) and squamous (Sq) NSCLC (CheckMate017 [4]) comparing nivolumab to docetaxel have demonstrated its efficacy at extending overall survival (OS) [5,6], and the interest of nivolumab in treating NSCLC has been confirmed in many subsequent studies in routine clinical practice [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The tumor size distributions shown in Figure 3 for patient KE-02 confirm this approach quantitatively. Another aspect is to optimize the dosage of Nivolumab, as it has been shown that low-dose Nivolumab could have comparable efficacy on cancer patients due to its flat dose-response relationship [50]. The flat relationship is mapped by the values of c 50 i , the drug concentrations yielding half-maximal response, that are by far lower than the body concentration steady states of the drugs when applied (cf.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that nivolumab could be a candidate for dose reduction 82 . No randomised trial data or regulatory authority supports ICB dose modification, but retrospective real‐world evidence in resource poor settings has found that low‐dose nivolumab (20–100 mg Q3W) had similar efficacy in a metastatic NSCLC cohort 101 …”
Section: The Pharmacology Of Immune Checkpoint Blockadementioning
confidence: 99%